2020
DOI: 10.9734/ajob/2020/v10i330109
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and Toxicity Analysis of Ricinus communis

Abstract: Medicinal plants play a vital role in ensuring proper health is attained by human beings due to their antioxidants constituents. The large family Euphorbiaceae contain nearly about 300 genera and 7,500 species. Amongst all, Ricinus communis or castor bean plant has high traditional and medicinal values towards a disease-free community. The objective of this study focuses on the phytochemical constituents and  phytotoxicity perspective of the R. communis plant. The castor bean plant is effective and is thought … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The soxhlet extraction of R. communis seed produced an amber-colored oil that was liquid at room temperature. Joshua et al (2020), Silma andDaneshwar (2016), andPushapalata et al (2014) have reported the presence of alkaloid, tannin, flavonoid, terpenoid, and phenol in R. communis seed oil. Except for flavonoids, Hashem et al (2015) found that the R. communis seed extract included alkaloids, tannin, saponin, and phenol.…”
Section: Discussionmentioning
confidence: 99%
“…The soxhlet extraction of R. communis seed produced an amber-colored oil that was liquid at room temperature. Joshua et al (2020), Silma andDaneshwar (2016), andPushapalata et al (2014) have reported the presence of alkaloid, tannin, flavonoid, terpenoid, and phenol in R. communis seed oil. Except for flavonoids, Hashem et al (2015) found that the R. communis seed extract included alkaloids, tannin, saponin, and phenol.…”
Section: Discussionmentioning
confidence: 99%